Preparation and Evaluation of PLGA-Safinamide Mesylate Nano Particles for the Management of Parkinson’s Disease - Sunkanna, Veena Kalyani; Joshi, Vedamurthy; Manjunath, Anoop (International Journal of Pharmaceutical Investigation, 2026)
Aim/Background Parkinson’s Disease (PD) is second most common chronic ongoing neurodegenerative disease recorded in ageing population, which is primarily treated with medications that either replace dopamine or mimic its effects in the brain. In this study, safinamide mesylate popular for its use during “off” episodes in PD was used. PLGA Nanoparticles of Safinamide mesylate (PNS) was prepared and evaluated to improve the bioavailability and targeted delivery of the drug. Materials and Methods PNS prepared by emulsion solvent evaporation method. Various trials were carried out to obtain particles in nano range with optimum drug entrapment. Three different batches of PNS were prepared by varying polymer concentrations. The prepared formulations were evaluated for particle size, zeta potential, drug loading, entrapment efficiency, XRD, TEM etc. and the In vitro release studies of the formulations were recorded. Results Batch PF1(1:1) had particle size of 606 nm, zeta potential of -30 mv, PDI of 0.224, entrapment efficiency of 22.69% and 11.35% of drug loading. Zeta potential was in the range of -24.2 to 30 mV, and zeta potential -30mV of PF1(1:1) ensuring stability. PXRD studies of PF1(1:1) showed amorphous state when scanned at 2θ and coated PNS was clearly identified from TEM images. The results of in vitro drug profiles studies were subjected to curve fitting, where PF1(1:1), followed Korsmeyer-Peppas model and value was 1.963 when compared to other batches. Accelerated studies showed no significant changes in drug content and in vitro release profile. Conclusion Hence it could be predicted that the prepared PNS, due to its inherent nano size will increase permeability of the drug and has the potential to decrease the Tmax and further improve bioavailability in management of Parkinson’s disease.
Keywords: Drug Loading; Entrapment Efficiency; Particle Size; PLGA Nanoparticle; PXRD